Implementasi Pendidikan Karakter melalui Lingkungan Sebagai Ruang Edukasi dalam Membangun Self Awareness dan Self Respect - Sri Handayani; Rita Sulastini (Journal on Education, 2023)
Every individual as part of the environment is actually responsible for playing an active role in protecting the environment for a better quality of life. In this interest, the environment as a public space functions dynamically in supporting various activities. This is where the contribution of each individual is needed in maintaining environmental quality. One way is by maintaining the continuity of the existence of the biological environment in order to maintain the order of the ecosystem. However, facts on the ground show that understanding of the environment is still limited to natural knowledge compared to taking applicable actions through practice in the field. This is not only the responsibility of the world of education, but requires the collaboration of all parties. One of them is through the guardian program or the foster program rolled out by the Wanadri organization with conservation-based educational content targeting all people, especially the younger generation. This research was conducted using a natural-ethnographic approach, considering that environmental preservation efforts are an alternative in providing education by local cultural approach. The purpose of this research is to construct, implement and evaluate the effectiveness of the program in fostering self-awareness and self-respect for each participant in various concrete actions. It is hoped that this program will become aspirational education, not only knowledge on the environment, but character building where each individual is part of a social life that is responsible in a sustainable manner